2022
DOI: 10.1007/s12144-021-02575-w
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric evaluation of the Russian version of the Gaming Disorder Scale for Adolescents

Abstract: Problematic gaming has become an emerging global health issue. Formal recognition of gaming disorder in the ICD-11 is a new opportunity for the discipline to conduct further investigation concerning the psychological consequences of problematic gaming. The present study investigated the psychometric properties and construct structure of the recently developed Gaming Disorder for Scale for Adolescents (GADIS-A), a multi-dimensional instrument that screens for gaming disorder symptoms, among Russian adolescent g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 85 publications
2
8
0
Order By: Relevance
“…To the best of the present authors’ knowledge, the present study is the first to translate and evaluate the psychometric properties of the Malay versions of the GDT and GADIS-YA among university students in Malaysia. Consistent with previous findings, the present study supported that the GDT has a single-factor structure (Cakiroglu & Alnak, 2021; Cudo et al, 2022b; Maldonado-Murciano et al, 2021; Montag et al, 2019; Pontes et al, 2021; Wang & Cheng, 2020) and the GADIS-YA has a two-factor structure (Mazaherizadeh et al, 2022; Nazari et al, 2022; Paschke et al, 2020). Furthermore, both the GDT and GADIS-YA demonstrated concurrent validity by significantly correlating with the IGDS9-SF, BSMAS, time spent on social media, and time spent on gaming.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…To the best of the present authors’ knowledge, the present study is the first to translate and evaluate the psychometric properties of the Malay versions of the GDT and GADIS-YA among university students in Malaysia. Consistent with previous findings, the present study supported that the GDT has a single-factor structure (Cakiroglu & Alnak, 2021; Cudo et al, 2022b; Maldonado-Murciano et al, 2021; Montag et al, 2019; Pontes et al, 2021; Wang & Cheng, 2020) and the GADIS-YA has a two-factor structure (Mazaherizadeh et al, 2022; Nazari et al, 2022; Paschke et al, 2020). Furthermore, both the GDT and GADIS-YA demonstrated concurrent validity by significantly correlating with the IGDS9-SF, BSMAS, time spent on social media, and time spent on gaming.…”
Section: Discussionsupporting
confidence: 92%
“…More specifically, the metric equivalence model suggested that factor loadings were similar across gender and gaming time groups, and the scalar equivalence model suggested that values and means were also equivalent across groups. Previous studies have confirmed the measurement invariance of the GDT (Cudo et al, 2022b;Maldonado-Murciano et al, 2021) and GADIS-A (Nazari et al, 2022) across gender. Cudo et al, 2022a found that female gamers tend to use smartphones as a gaming platform, spend less hours in gaming per week, and experience lower levels of online flow as compared to male gamers.…”
Section: Gadis-ya_i9mentioning
confidence: 58%
See 1 more Smart Citation
“…The construct validity findings supported Paschke et al [ 38 ] two-factor model. These results are congruent with Nazari et al [ 41 ], who also discovered a two-factor structure for this instrument.…”
Section: Discussionmentioning
confidence: 99%
“…Paschke et al [ 38 ] reported that Cronbach’s alpha for the total GADIS-A scale is 0.91, 0.9 for the NS factor subscale, and 0.87 for the CBS factor subscale. The GADIS-A has also been validated among Russian adolescents, and Cronbach’s alpha reported 0.891 [ 41 ].…”
Section: Methodsmentioning
confidence: 99%